Preparation dishwashing soap from Kaffir lime and papaya at the Faculty of Education, Souphanouvong University Academic Year 2020 – 2021 - SOURVATHAO, Vixai; LITTHAVONG, Somvang; VANGCHANGYIA, Somsack; PHONGSAVATH, Sengthavy; YONGYE, Noulongxiong (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of this study “preparation dishwashing soap from kaffir lime and papaya at the Faculty of Education” was to study preparation dishwashing soap from kaffir lime and papaya, to compare pH of this dishwashing soap to pH of dishwashing soap production call Lipon and to ask satisfaction of using the dishwashing soap from kaffir lime and papaya. The sample of this study was teachers and students at dormitory of Faculty of Education, Souphanouvong University. The number was 30 people including 25 females. The materials used to measure was satisfaction form for teachers and students which includes characteristics and positive effects. Besides, PH-035Z Waterproof pH/Temperature Meter was used to measure pH while SPSS was used to analyze data such as Mean () and Standard Deviation (). The result was that dishwashing soap from Kaffir lime and papaya is similar to Liponf. This soap was a single content with a lot of bubble and stable babble and this soap can clean fat out very well. Also this substance can solute in water but it is more diluted then Liponf. It shows that they are similar but pH of dishwashing soap from kaffir lime and papaya was 6.92 while Liponf was 6.97. The satisfaction data analysis of teachers and students 30 people, 25 females at the Faculty of Education, Souphanouvong University shows that they satisfied with the useful of this soap. They had less satisfaction of the soap characteristic which Mean was 4.57 (=4,57) and Standard Deviation was 0,20 (S.D = 0.20). The satisfaction of teachers and students demonstrates that they satisfied in high level for using dishwashing soap which prepared from Kaffir lime and papaya.